THE EFFECT OF TAX PLANNING AND INTELLECTUAL CAPITAL ON FIRM VALUE (Case Study on Food and Beverage Companies Listed on The Malaysia Exchange in 2019-2021) - Neng Susan Nurjanah; Daeng M. Nazier (Journal of Taxation Analysis and Review, 2023)
The purpose of this study is to determine the effect of tax planning and Intellectual Capital on Firm Value in manufacturing sektor companies with the food and beverage sub-sektor listed on the Malaysia Stock Exchange. The sampling technique used multiple linier regression analysis with a sampling technique that is purposive sampling with with a sampling of 39 samples. The study uses the SPSS 22 analysis tool. The results showed that (1) tax planning had no significant effect on firm value, (2) Intellectual Capital had an effect positive on firm value.